Tumpang Sari Padi Gogo dan Kedelai Dengan Konsep Leisa: Limbah Pertanian Sebagai Pupuk Organik - Edi Susilo; Parwito Parwito (University of Prof. Dr. Hazairin, SH, 2013)
Food needs are increasing as population growth. Low productivity and limited land were the problem to fulfill the need of food. One of the solutions is agricultural intensification by intercropped cultivation system with LEISA concept. Provision of inputs such as organic fertilizers can improve the physical, chemical and biological properties of soil. This study was aimed to gain time and type of organic fertilizer application. The results showed that the time of the application of organic fertilizer did not affect significantly rice and soybean growth. However the type of organic fertilizer affected significantly rice and soybean growth. Chicken manure was the best fertilizer material on rice vegetative phase and soybean vegetative and generative phase. The interaction between time and type of organic fertilizer application influences significantly soybean growth, and the best treatment was two weeks before planting and chicken manure.